RGO/AuNPs/tetraphenylporphyrin nanoconjugate-based electrochemical sensor for highly sensitive detection of cadmium ions. Issue 29 (10th July 2018) - Si, Yanmei; Liu, Jing; Chen, Yuan; Miao, Xufeng; Ye, Fang; Liu, Zhigang; Li, Jishan
Abstract : rGO/AuNPs/TPP nanoconjugates were prepared and used to construct a novel electrochemical sensor for the sensitive and selective detection of cadmium ions. Abstract : In this study, a novel electrochemical sensor is proposed based on reduced graphene oxide (rGO)/gold nanoparticles (AuNPs)/tetraphenylporphyrin (TPP) (rGO/AuNPs/TPP) nanoconjugates for the detection of cadmium ions (Cd 2+ ). The sensing mechanism is based on the coordination interaction between metal cations and porphyrin. rGO was employed to accelerate the incorporation of Cd 2+ and tetraphenylporphyrin. Besides, AuNPs were introduced to enhance the sensitivity of electrochemical detection. Accordingly, the proposed electrochemical sensor showed high selectivity toward Cd 2+ over other metal ions. Moreover, the obtained findings indicated high sensitivity, broad linear range from 50 nM to 300 μM, and a low detection limit, which was lower than the values recommended by the United States Environmental Protection Agency (EPA) and World Health Organization (WHO). The sensor was further applied to determine Cd 2+ in real water samples with satisfactory results.